Dynamics of seasonal rabies incidence in animals in Azerbaijan - Ch. V. Aliyeva; Sh. K. Zeynalova (Ветеринария сегодня)
The increasing number of rabies outbreaks is currently one of the most important challenges in both human and animal health. The epidemiological and epizootic significance of rabies is determined by its absolute lethality in case of clinical manifestations, as well as global spread, latent incubation period and lack of specific treatment. Rabies is endemic in Azerbaijan; wild carnivores, stray dogs and cats determining the natural type of rabies are considered the main source of infection in the Republic. The dynamics of rabies natural cases has seasonal variability. As a rule, the number of disease cases increases in autumn, winter and spring, which is associated with the biological characteristics of the main disease vectors and the climatic conditions in the region. The main purpose of the study was to investigate the spread of rabies in Azerbaijan in different seasons of the year. For this purpose, the statistical data were collected based on animal incidence by month and season for the last four years (2018–2021). It was found that rabies cases were most often identified in the period from March to May: in 2018 – 21 (31%) cases, in 2019 – 24 (38%) cases, in 2021 – 8 (40%) cases. The exception was 2020, when the majority of rabies cases occurred in December – February. To assess the epizootological and epidemiological risks of rabies in the country, the disease frequency rate among various animal species was studied by year. The largest number of rabies cases (54%) was shown to be detected among dogs. Cattle accounted for 38.1% of cases, 5.7% of positive samples were derived from stray dogs, 1.6% – from sheep, 0.6% – from horses. The study results have shown that animal rabies exhibits a clearly pronounced seasonal pattern in the Republic of Azerbaijan.